Exploring the Societal Aspirations of Youth in Himachal Pradesh, Bharat (Indian Journal of Social Science and Literature (IJSSL), 2024)
This article draws from a research study conducted on domiciled youth of Himachal Pradesh. The objective of the study was to understand the social aspirations of youth in the state and their plans to contribute towards the society. Mixed method approach was used to fulfil the objectives of this study. The respondents selected for the study were youth who were between 20-25 years of age and were enrolled in professional courses in various Higher Education Institutions located in Himachal Pradesh. The respondents were selected using multistage non-probability purposive sampling technique. Primary data was gathered using a structured interview schedule from 280 respondents and Focused Group Discussions. The study found that the respondents were desirous of serving the society after getting employed. The major areas in which they wished to contribute after settling down in life were welfare of youth with problems, education, and welfare of Gaumata (cows of local breed). The study also found that though a majority of respondents were also keen to become community leaders, very few showed interest in participating in electoral politics.